Who are the wine and food festival visitors? : an exploratory study - Marković, Suzana, ekonomistica (Array, 2019)
Hosting wine festivals provides the opportunity to organizers and wine destinations to offer a wide range of experiences that differ from the day-today way of life and, in a sense, are the best way to provide a wine tourism lifestyle experience. The aim of the research was to measure the wine and food personality traits of festival visitors, specifically involvement and neophobia, and explore their relationship with the experience quality dimensions of the festival (environment, education, service providers, functional benefits, entertainment) and experience outcomes (satisfaction, loyalty). Additionally, research aimed to compare wine and food involvement and neophobia with regard to specific demographic characteristics of the visitors (gender, income level, visitor status, employment, residency). Data collection was done during the VinoCOM festival on 24th and 25th November 2017 in Zagreb using an on-site questionnaire. Descriptive and bivariate statistical analyses were used to analyze collected data. The results obtained show a significant and positive relationship between wine and food involvement and experience quality as well as experience outcomes. At the same time it is confirmed a negative relationship between wine and food neophobia, experience quality and experience outcomes.